(untitled) (Journal of Comparative & International Higher Education, 2023)
This article explores Iranian international students’ (IISs) experiences of human dignity (HD) within Canadian universities. Drawing on in-depth interviews with 24 current and former IISs, We created a conceptual HD framework to analyze the data. Three themes emerged as key to IISs’ experiences of HD in the context of postsecondary education: 1) the relationship between students and university faculty/staff, 2) gender equality and freedom, and, 3) having a minority or marginalized identity. We conclude with observations about how an awareness of students’ HD experiences could strengthen the support offered to international students (ISs).